Multimodality imaging in the diagnostic management of concomitant aortic stenosis and transthyretin-related wild-type cardiac amyloidosis - Cersosimo, Angelica; Bonelli, Andrea; Lombardi, Carlo M.; Moreo, Antonella; Pagnesi, Matteo; Tomasoni, Daniela; Arabia, Gianmarco; Vizzardi, Enrico; Adamo, Marianna; Farina, Davide; Metra, Marco; Inciardi, Riccardo M. (Frontiers in Cardiovascular Medicine, 2023)
Severe aortic stenosis (AS) is the most common valvular heart disease with a prevalence rate of more than 4% in 75-year-old people or older. Similarly, cardiac amyloidosis (CA), especially “wild-type transthyretin” (wTTR), has shown a prevalence rate ranging from 22% to 25% in people older than 80 years. The detection of the concomitant presence of CA and AS is challenging primarily because of the similar type of changes in the left ventricle caused by AS and CA, which share some morphological characteristics. The aim of this review is to identify the imaging triggers in order to recognize occult wtATTR-CA in patients with AS, clarifying the crucial step of the diagnostic process. Multimodality imaging methods such as echocardiography, cardiac magnetic resonance, cardiac computed tomography, and DPD scintigraphy will be analyzed as part of the available diagnostic workup to identify wtATTR-CA early in patients with AS.